Protectionism and Containment in the Twenty-First Century: Trans-Pacific Partnership (TPP) - Chang, Claude V; Kluegel, Karl (International Journal of Management and Sustainability, 2015)
This paper advances two premises in regard to the Trans-Pacific Partnership (TPP): The first is that TPP represents the latest initiative on the protectionism continuum, thus the latest substitute for domestic adjustment. As argued, its primary focus is to facilitate the perceived need to “rebalance global growth” within the existing institutional framework of global capitalism with minimal disruption to the US economy, hence it is unlikely to succeed in an era of increasing uncertainty surrounding the world economic and political order in a post-Great Recession world.. The second premise is that, as a two-pronged initiative TPP further represents the latest attempt to contain China in its sphere of influence in the region and the wider world, hence it is equally likely to fail in this objective given China’s established geo-economic role in the region and its use of soft power.